PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE INSIDE OUTSIDE CIRCLE (IOC) TERHADAP HASIL BELAJAR - Endar Sulistyowati (Jurnal AlphaEuclidEdu, 2021)
The purpose of this study was to determine the effect of the Inside Outside Circle (IOC) cooperative learning model on the learning outcomes of eighth grade students of SMP Negeri 4 Metro. The method that will be used in this study is a true experimental design using a pretest-posttest control group design. This research was conducted by 22 students of class VIII B SMP Negeri 4 Metro even semester as samples. After receiving treatment using the Inside Outside Circle (IOC) type of cooperative learning model, student learning outcomes have increased seen from the comparison in the pretest and posttest evaluations, namely students who achieve KKM in the pretest evaluation are 27.27% or 6 students from a total of 22 students. While the students who achieved the KKM in the posttest evaluation were 68.18%, namely 15 students from a total of 22 students. This is evidenced again by the calculation of data analysis using the Simple Linear Regression formula obtained = 55.5505+ b = 0.3183 so that Y = + bx is( Y) =55.5505+0.3183x and the analysis calculation that t_hitung> t_tab which is seen at a significant level of 5%, namely 2.90 > 1.72. And at a significant level of 1%, namely 2.90> 2.53. Which can be seen in the table G statistics. Thus, the hypothesis is accepted. So it can be concluded that "there is a positive influence of the Inside Outside Circle (IOC) type of cooperative learning model on the learning outcomes of class VIII students of SMP Negeri 4 Metro in even semesters"